2019
DOI: 10.2196/10465
|View full text |Cite
|
Sign up to set email alerts
|

User Preferences and Persona Design for an mHealth Intervention to Support Adherence to Cardiovascular Disease Medication in Singapore: A Multi-Method Study

Abstract: Background The use of mobile health (mHealth) has gained popularity globally, including for its use in a variety of health interventions, particularly through short message service (SMS) text messaging. However, there are challenges to the use of mHealth, particularly among older users who have a large heterogeneity in usability and accessibility barriers when using technology. Objective In order to better understand and conceptualize the diversity of users and give ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 25 publications
0
31
1
2
Order By: Relevance
“…Based on data from a variety of sources, including focus groups, national surveys, and social media, we identified and presented unique beliefs, attitudes, motivations, lifestyles, and communication styles related to the HPV vaccine, synthesized through four personas. While personas have been used in social marketing and health research ( 32 , 41 , 42 ), we found little evidence of persona development for social media interventions.…”
Section: Discussioncontrasting
confidence: 63%
“…Based on data from a variety of sources, including focus groups, national surveys, and social media, we identified and presented unique beliefs, attitudes, motivations, lifestyles, and communication styles related to the HPV vaccine, synthesized through four personas. While personas have been used in social marketing and health research ( 32 , 41 , 42 ), we found little evidence of persona development for social media interventions.…”
Section: Discussioncontrasting
confidence: 63%
“…In recent decades, the rise of person-centred policies along with an increasing computerisation of information has seen the use of personas spreading. For example, in the health sector, personas have been used when developing public health messages and eHealth platforms for patients [ 45 , 46 , 47 ], during the design of medical equipment [ 48 , 49 , 50 ], and when developing health policy [ 51 ]. Personas of older people have been incorporated in health informatics [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Personas have proven to be a crucial factor when designing user tests through several research. In their research for user preferences and persona design in cardiovascular disease, Haldane et al [ 38 ] reported that personas are a key feature of user-centered design and are used in many fields from design to marketing and product, and it aims at understanding large and diverse target audiences. Therefore, our study will also focus on studying personas to identify diverse patient groups.…”
Section: Methodsmentioning
confidence: 99%